The strategy process contexts and cases - Quinn, James Brian 1928- (Prentice Hall, 1993)
Focusing on real issues in a full historical context, this compilation of cases illustrates the many complex threads of research and successful practice in the strategy field today. The book features cases which focus on international competition and represent the global dimensions of today's major strategy issues. Some of these cases involve both Japanese and European companies and their competitive strategies; analyze new joint ventures in worldwide competition; and raise issues that are on the cutting edge of strategy in the early 1990s (ie. Honda, Ford, Team Taurus).